Influence of Inlet Position on the Amount of Pollutant Particles Trapped Along the Flow Path of Slow Sand Filter (SSF) Pipe Utilized for Filtering Swamp Water - Sigit Mujiharjo; Syafnil Syafnil; Ilma Donna Astri Harahap (AGRITROPICA : Journal of Agricultural Sciences, 2018)
This study aims to explain the effect of inlet position of a Slow Sand Filter (SSF) Pipe on the amount of pollutant particles caught along the flow path in the SSF Pipe. The main equipment used is nine pieces of SSF Pipe, each has 4 inches in diameter and 50 cm in length with Pantai Panjang Bengkulu’ssand as the filter medium. The inlet positions tested were 90°, 45° and 0°; repeated three times and arranged in a completely randomized design (CRD). The observed variable is the weight of the captured pollutant in the SSF at the distance of 10cm, 20cm, 30cm, and 40cm from the inlet. Results of the research showed that the number of pollutant particles caught along the flow path in the SSF decreased following a linear model as the distance from the inlet was increased. The number of pollutant particles caught also decreased with the decrease of inlet position slope. The inlet position significantly affected the number of pollutant particles caught along the flow path; the position of 90° causes the highest amount of pollutants to be caught and significantly differs from that of the position of 45° and 0°. The position of 0° causes the least amount of pollutants to be captured that considered to be the best inlet position so far. It is important; however, to research whether inlet position of more than 180° could result in a much smaller amount of pollutant caught along the flow in the  SSF Pipe.Keywords: SSFPipe, inlet position, particle caught in SSF, peat water filtration